1990 ネン 3 ガツ ボフォート カイ カイヒョウ イキ デノ カイヨウ セイブツ チョウサ ホウコク - 渡辺, 研太郎; ワタナベ, ケンタロウ; 川口, 弘一; カワグチ, コウイチ; Kelly, Brendan; Watanabe, Kentaro; Kawaguchi, Kouichi (1991)
P(論文) 文部省科学研究費・国際学術研究, "北極海海氷域における基礎生産とエネルギー移動の時系列的変動の研究"の一環として, 平成2年3月1日から13日までの間, ボフォート海沿岸のプルドー湾, バロー岬沖で海洋生物氷上観測を行った。プルドー湾では4点で採氷, 海氷採取, ネットによるプランクトン採集およびトラップによる底生生物採集を行ったほか, 採集した底生小型甲殻類について, 測定例の少ない冬期間の代謝速度を知るため, 呼吸量も測定した。バロー岬沖では, アザラシの餌となる底生生物をトラップにより採集した。また海洋生物氷上調査を行う際の現地での設営, 実験室の設備などについて実地に調査し, 情報を収集した。 As part of the Mombusho International Scientific Research Program, "Temporal variability of primary production and energy flow in the Arctic sea ice area (PREFLA)", on-ice marine biological investigations were carried out from March 1-13,1990,in Prudhoe Bay and off Pt. Barrow, Beaufort Sea. Water and sea-ice core collections, plankton samplings with nets and collections of benthic organisms with traps were performed at four locations in Prudhoe Bay. Respiration rates were measured for small benthic crustaceans from Prudhoe Bay with special interest in metabolic rate in the winter season. Trap samplings were also performed at one location off Pt. Barrow to know benthic fauna in relation to seal's diet. In addition, we obtained information on the logistic support and laboratory facilities for the future marine biological research program in that area. departmental bulletin paper